Thermal endoscope based on cost-effective LWIR camera cores - Dumitru Scutelnic; Giacomo Marchioro; Salvatore Siracusano; Paolo Fiorini; Riccardo Muradore; Claudia Daffara (HardwareX, 2022)
The implementation of a thermal endoscope based on the LWIR camera cores Lepton and a custom miniaturized electronics is reported. The sensor and the PCB can be inserted into a cylindrical protective case of diameter down to 15mm, inox tube or plastic, 3D printable envelope, with an optical window in Germanium. Two PCBs were developed for assembling the endoscope in two different schemes, to enable frontal or lateral thermal vision setup. The thermal endoscope unit is controlled by a Raspberry external unit. The Infrared Vision Software is provided for controlling the acquisition of thermal frames, and for the thermographic calculation of the object temperature from the input parameters on object surface emissivity and environment. In general, the device enables to perform thermography in applications in which traditional larger equipment cannot be employed, as nondestructive diagnostics in confined space in the engineering field. The thermal endoscope was designed with dimensions also compatible for robotic-assisted/traditional minimally-invasive surgery.